John Thelwall
XV, 324 p.
Keywords: Drawing on newly-discovered manuscripts, this collection is the first modern edition of poetry by John Thelwall, the famed radical Romantic and champion of the working class. Eight key essays and 125 fully-annotated poems introduce his work in correspondence with historical traditions and current critical paradigms.